Effect of Folic Acid on Homocysteine Level in Ischemic Stroke Patients in a Tertiary Level Hospital in Rajshahi. - Haque, Lotifa; Habib, Md Anwar; Ali, Md Yousuf; Nilufar, Sonia; Alam, Tarifat; Hoque, Md Emdadul (KYAMC Journal, 2022)
Background: A number of risk factors are responsible for ischemic stroke some are modifiable and some are not modifiable. Homocysteine is a modifiable, independent risk factor of ischemic stroke. Objective: To evaluate the effectiveness of folic acid on homocysteine levels in ischemic stroke patients. Materials and Methods: This study was an experimental study carried out in the Department of Pharmacology and Therapeutics, Rajshahi Medical College in collaboration with the Department of Neurology, Rajshahi Medical College Hospital from July 2016 to June 2017. A total number of 90 ischemic stroke patients diagnosed by CT scan findings who came for treatment in the Neurology department of Rajshahi Medical College Hospital were enrolled in this study. Simple random sampling is done. The patients were divided into two groups: experimental group (45 patients) who were treated with 5mg folic acid along with other traditional treatment, control group (45 patients) who were treated by only traditional therapy given by the neurology department. Before starting treatment, along with other investigations, serum homocysteine level of both experimental and control groups was estimated. After three months of continuous treatment with folic acid in the experimental group, the serum homocysteine level of both groups was measured again. Data were analyzed using SPSS version 16 for windows. Results: The results showed that there was a small numerical difference in homocysteine level before and after treatment in the experimental and control group, yet the change was statistically significant in the experimental group after three months of treatment with 5mg folic acid. Conclusion: It is revealed that use of folic acid may play an important role in reducing homocysteine level in ischemic stroke patients. KYAMC Journal Vol. 13, No. 01, April 2022: 13-17